Фразеологическая интерференция (на материале литовского языка в условиях контакта с английским) - Пажусис, Лёнгинас (Kalbotyra, 1983)
The present paper deals with the phenomena of interference which involves the so-called phraseological units (i. e. phrases or even sentences whose meanings are not obvious through knowledge of the individual meanings of the constituent words). The linguistic corpus was elicited from Lithuanian periodicals published in the USA and Canada as well as from the speech of immigrants whose primary language, Lithuanian, has for several decades been in contact with American English. According to the level of phraseological units involved in the process of interference, three major types of phraseological interference (within the sphere of substitution) are distinguished: semantic, structural-semantic and a combination of the two.